An Evaluation Of E-Government Performance In Nigeria: A Public Value Approach - Abdulrazaq Kayode, Abdulkareem (2021)
This research’s contribution lies in the fact that this study is applied the public values to measure the net benefits of e-government. Also, digital literacy has proven to be a good predictor for actual use, user satisfaction and the public value of e-government. This study also established the moderating effect of citizens’ access to ICT between the use and public value of e-government. This study’s conceptual model can be used in future studies to evaluate specific ICT inclined systems’ success.